Mealybugs (Hemiptera: Pseudococcidae) on ornamental plants in West Java, Indonesia with a new country species record, and their natural enemies (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Viorenta, Sartiami D, Maryana N, Watson GW, Zarkani A. 2025. Mealybugs (Hemiptera: Pseudococcidae) on ornamental plants in West Java, Indonesia with a new country species record, and their natural enemies. Biodiversitas 26: 1018-1029. Part of Indonesia's biodiversity in ornamental plants has been developed for the global market. However, one of the constraints in meeting market demand is the presence of mealybug pests, which can reduce plant beauty, vigor, and economic value of plants. This study identifies mealybug species associated with ornamental plants in Indonesia and their natural enemies based on morphological characteristics. The research found 15 mealybug species, 14 of which had been previously recorded in West Java, Indonesia, namely Dysmicoccus brevipes, D. neobrevipes, Exallomochlus hispidus, Ferrisia virgata, Maconellicoccus hirsutus, Nipaecoccus nipae, Paracoccus marginatus, Phenacoccus solenopsis, Planococcus lilacinus, Pl. minor, Pseudococcus jackbeardsleyi, Ps. longispinus, Rastrococcus iceryoides and R. spinosus. The fifteenth species, Spilococcus mamillariae, found on cacti, is a new record for Indonesia and Southeast Asia. This study also documented various natural enemies, including both predators and parasitoids. Seven predator species were identified, six of which belonged to Coleoptera: Coccinellidae, namely Cryptolaemus montrouzieri, Curinus coeruleus, Illeis sp., Nephus sp., Cheilomenes sexmaculata, and Scymnus sp.; and one species of Neuroptera: Chrysopidae: Plesiochrysa ramburi. Hymenopteran parasitoids were found belonging to two families: Encyrtidae (Anagyrus pseudococci, A. mirzai, Blepyrus insuliaris and Gyranusoidea tebygi; and Eulophidae (Aprostocetus sp.). Furthermore, Hymenopteran hyperparasitoids belonging to the families Aphelinidae (Promuscidea unfaciativentris) and Encyrtidae (Prochiloneurus sp. and Prochiloneurus nagasakiensis) were also recorded
Keywords: Anagyrus, cacti, Cryptolaemus montrouzieri, morphology, Spilococcus mamillariae